The Prevalence of Hepatitis B Virus in High Risk Groups in Nineveh Governorate / Iraq (Baghdad Science Journal, 2025)
Hepatitis B is an inflammation of the liver that caused by Hepatitis B virus (HBV) which is DNA virus that infects the human and some kinds of animals such as chimpanzees and birds. This disease considered as the major disease of mankind and a serious global public health problem. HBsAg, HBeAg, HBcAb, HBeAb and HBsAb are markers used to detect the presence and the stage of infection. The current study included (181) individuals from both sexes, (137) males and (44) females. By ratio 3.11: 1.The mean age of patients 2.4033 ± 0.83519 (range 18-73) years as follows < 20 (11.6%), 21–40 (47.5%), 41–60 (29.8%) and > 60 (11.0%) . These patients are 73 (40.4%) Blood donors from Central Blood Bank, 88 (48.6%) Chronic kidney failure at Ibn – Sina Teaching Hospital and 20 (11.0%) Thalassemic patients at Ibn – Alatheer Teaching Hospital, Nineveh Governorate / Iraq. For the period from July 2011 till May 2012.The results indicated that the number of serum patients infected with HBV was 90 (49.7%) using Enzyme Linked Immuno Sorbent Assay technique. These patients had many markers named HBsAg, HBeAg, HBcAb, HBeAb and HBsAb with percentages 90 (49.7%), 47 (26.0%), 89 (49.2%), 53 (29.3%) and5 (2.8%) respectively. Ninety three patients infected with HBV ninety of them gave positive results using ELISA and rt-PCR technique, and three gave positive results using rt-PCR only inspite of their negative results in ELISA. We concluded that HBV infection remains a serious issue because it's prevalence is still significant among patients, all viral markers are very important for the diagnosis of infection, rt-PCR is a very sensitive scientific technique gave the exactly number of copies/ml in a closed system.